The role of social media Instagram of community towards tourism promotion in Baubau City - Hastuti, Hastuti; Andy Ary Maulana, Andy Ary Maulana Wijaya; iska, Iska (Universitas Ahmad Dahlan, 2022)
Tourism potential of Baubau City tends to be unable to compete in promotion with several other regions. Tourism policies carried out by local governments have not been able to make tourism as the main asset of the City of Baubau. This study examines the role of community social media in the promotion of tourism in the City of Baubau, especially on Instagram social media accounts. The study focused on Instagram accounts that have tourism content, and conducted searches that have the most posts about attractions. The research method used is descriptive qualitative. Next to check the validity of the data, what the researchers did was to make prior observations on various relevant Instagram accounts at random. Then the data that has been obtained is confirmed, described, categorized which views are the same, different and which are specific from the data sources. Finally, the data are analyzed by researchers to produce conclusions. The analysis technique used by these researchers is the analysis of source and content triangulation techniques. The results showed that the community account on Instagram is very helpful in providing promotion for tourism in the City of Baubau, besides the popular hashtags that are used to make it easy for people to get information about content, location and access to several tourism objects in the City of Baubau.